Distorted self-perception and dissatisfaction with body image among nursing students - Luciane Simões Duarte; Milena Namie Koba Chinen; Elizabeth Fujimori (SciELO, 2021)
ABSTRACT Objective: To evaluate distorted self-perception and dissatisfaction with body image among nursing students. Method: Cross-sectional study with students from a public university. Self-perception and satisfaction with body image were assessed using the Figure Rating Scale and the Body Shape Questionnare (BSQ). Body Mass Index was calculated with self-reported weight and height. Analysis was processed in Stata 15.0 with a significance level of 5%. Results: A total of 93 students participated in the study. Results showed 87.1% of distorted self-perception, with a greater proportion of students who overestimated their body size (68.8%); 89.2% of students were dissatisfied with their body image according to the Figure Rating Scale, and 55.9% according to the BSQ. Dissatisfaction assessed by the BSQ was associated with biological sex, nutritional status, diets and bullying. Conclusion: The results indicate the need to address the theme in the training of nurses, to help them accept their own bodies and to enable them to act effectively in their professional practice.